2022
DOI: 10.1002/fsn3.2854
|View full text |Cite
|
Sign up to set email alerts
|

Garlic oil alleviates high triglyceride levels in alcohol‐exposed rats by inhibiting liver oxidative stress and regulating the intestinal barrier and intestinal flora

Abstract: Garlic oil (GO) is a kind of natural extract extracted from garlic, which has strong antioxidant activity. This study elucidates the protective mechanism of GO against alcohol‐induced high triglyceride levels. Sixty male Sprague Dawley rats were assigned to five groups, including a control group (CON), a model group (MOD) treated with alcohol 56% v/v at 8 ml kg −1 day −1 for 2 weeks then 10 ml kg −1 day −1 for 8 weeks, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…A total of five samples were randomly selected from each group for sequencing. The sequencing methods were adopted from our previous studies ( 24 , 25 ). In detail, DNA was extracted using a DNA kit (Tiangen Biotech (Beijing) Co., Ltd.) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…A total of five samples were randomly selected from each group for sequencing. The sequencing methods were adopted from our previous studies ( 24 , 25 ). In detail, DNA was extracted using a DNA kit (Tiangen Biotech (Beijing) Co., Ltd.) according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…[22] Increasing dietary ber intake could lower postprandial plasma glucose levels by delaying gastric emptying and slowing food digestion and absorption [23]. For lipid metabolism, dietary ber can be fermented and metabolized by intestinal ora to generate SCFAs such as acetate, propionate, and butyrate, which are bene cial for increasing energy consumption and reducing TG accumulation in the liver [24]. An open-label randomized trial was conducted by Wang et al, who reported that a high-content complex dietary ber intervention signi cantly improved the levels of FBG, 2hBG, TG, TC, and LDL-C in GDM women [25].…”
Section: Discussionmentioning
confidence: 99%
“…Garlic oil (GO) is a naturally derived vegetable oil from garlic. It has commonly been associated with numerous health benefits ( 6 ). GO mainly consists of sulfides such as diallyl sulfide (DAS), diallyl disulfide (DADS), diallyl trisulfide (DATS), diallyl tetrasulfide (DATTS) and other similar compounds ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%